(untitled) - Vrabel, Jan; Hudak, Anton (Doprava a spoje, 2010)
This article looks at monitoring of the vehicles which are using the GPS technology. At the beginning we have talked about the GPS system and consequently its application by vehicles monitoring in status on line communication. In the article are analysed some disadvatages occured by monitoring the changes of cubage of the power fuel